Change in externalizing problems over time among ethnic minority youth exposed to violence. (November 2017) - Ayer, Lynsay; Setodji, Claude; Schultz, Dana; Jaycox, Lisa H.; Kofner, Aaron
Abstract: Youth exposed to violence, many of whom are from racial/ethnic minority backgrounds, are at high risk for externalizing problems such as aggressive and oppositional behavior, conduct problems, and delinquency. Most interventions target youth with already high levels of such problems, while selective prevention efforts have received less attention. It is important for researchers, policy makers and practitioners to understand how such problems develop and change over time, and how selective prevention may impact externalizing problems. In this study, we examined one-year trajectories of externalizing problems in 883 low-income, ethnic minority youth exposed to violence who participated in randomized controlled trials testing a prevention program for high-risk youth called the Strengthening Families Program. We found three trajectories of externalizing problems: Low Externalizing (43% of the sample had consistently low levels of externalizing symptoms), Persisters (39% of the sample had consistently high levels of externalizing symptoms), and Improvers (18% of the sample had initially high levels of externalizing symptoms that decreased over time). There were demographic differences between the three trajectories with individuals in the Low Externalizing trajectory more likely to be female and younger than those in the other two trajectories and Persisters and Improvers had significantly more problems with baseline internalizing symptoms, family conflict, and parenting behavior compared to the Low Externalizing trajectory. Logistic regressions then tested several predictors of membership in the Persisters trajectory compared to the Improvers trajectory, controlling for all covariates simultaneously. Only baseline parenting behavior and intervention group membership significantly predicted trajectory membership, and these were small and unreliable effects. Thus, children with varying levels of violence exposure, co-occurring emotional/behavioral problems and family issues, and varying demographics (e.g., age and gender) may do equally well over time, but engagement in this type of intervention may increase the likelihood that high levels of externalizing problems are ameliorated over time. Highlights: 883 ethnic minority youth exposed to violence participating in a preventive intervention were followed over one year. Three trajectories of externalizing problems were found: low externalizers, persisters, and improvers Youth who had received the intervention were more likely to be improvers than comparison youth. There is a need to identify more predictors of externalizing trajectories in this population.